Mapping Uncharted Territory: Launching an Online Embedded Librarian Program. Issue 1 (2nd January 2017) - Allen, Seth
ABSTRACT: Developing a strategy for embedding librarians in online courses can be challenging, but it is essential to demonstrate to accrediting agencies how libraries serve online students. A well-thought-out plan can be scalable and sustainable for rapidly growing online programs and can satisfy accreditation standards. This article examines how one small, liberal arts college developed a plan of action for an online embedded librarian program, including both the conceptual and practical aspects of launching the program: aligning library instruction with course and program learning outcomes, brainstorming strategies for embedded library instruction, and communicating the value of such a program to online teaching faculty.